Exploring new frontiers of electronic publishing in biomedical science - Ng, K.H. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
Publishing is a hallmark of good scientific research. The aim of publishing is to disseminate new research knowledge and findings as widely as possible in a timely and efficient manner. Scientific publishing has evolved over the years with the advent of new technologies and demands. This paper presents a brief discussion on the history and status of electronic publishing. The Open Access Initiative was created with the aim of overcoming various limitations faced by traditional publishing access models. Innovations have opened up possibilities for electronic publishing to increase the accessibility, visibility, interactivity and usability of research. A glimpse of the future publishing landscape has revealed that scientific communication and research will not remain the same. The internet and advances in information technology will have an impact on the research landscape, scholarly publishing, research policy and funding, dissemination of knowledge, and the progress of science as a whole.